A comprehensive workbook for preparatory English - Ho, Chui Chui
A Comprehensive Worklok for Preparatory English has been written primarily with the fresh undergraduates of Universitt Teknologi MARA (UITM) in mind. Most of them are required to take the Preparatory English course which is a one-semester program designed to remedy their weaknesses in the use of English and to raise their proficiency level. Although this workbook is aimed at this group of learners, it can serve as a uselul resource for anyone taking a basic English course. The objective of this workbook is to provide ample practices to prepare the undergraduates for their mid-semester and final examinations It covers the major areas of: Reading Comprehension Grammar Writing An answer key is provided for each practice making this work book a valuable source for self -study as well as for classroom instruction.